The Influence of Organization’s Culture and Internal Control to Corporate Governance and is Impact on Bumn (State-Owned Enterprises) Corporate Performance in Indonesia - SARI, Maya; LUBIS, A de Fatma; MAKSUM, Azhar; LUMBANRAJA, Prihatin (Journal of Advanced Research in Law and Economics, 2018)
This study measured four variables, namely, organizational culture, and internal control as exogenous variables as well as corporate governance and corporate performance as an endogenous variable. To collect data using survey techniques on state-owned companies in Indonesia. Respondents of this research are the manager of state-owned enterprises in Indonesia as many as 270 respondents. Validity and reliabilities made to the questionnaire that has been collected. The data were analyzed using Structural Equation Modeling with LISREL application. The results showed that there is significant influence of organizational culture on corporate governance, internal control of corporate governance, organizational culture on corporate performance, and corporate governance influence on corporate performance. From the test direct effect has no significant effect of internal control to corporate performance. Corporate governance is an intervening variable relation between the internal control and corporate performance.